Trimodality therapy for oropharyngeal cancer in the TORS era: Is there a cohort that may benefit?. Issue 9 (17th April 2019) - Gallitto, Matthew; Sindhu, Kunal; Wasserman, Isaac; De, Brian; Gupta, Vishal; Miles, Brett A.; Genden, Eric M.; Posner, Marshall; Misiukiewicz, Krzysztof; Bakst, Richard L.
Abstract: Background: With increasing adoption of transoral robotic surgery (TORS) for oropharyngeal cancer (OPC), more patients may receive trimodality therapy. We sought to investigate outcomes and toxicities in this cohort. Methods: A retrospective study of patients with OPC treated with trimodality therapy at a tertiary‐care hospital, comparing those receiving bilateral vs unilateral neck radiation. Results: Four hundred thirty‐six patients underwent TORS, 17% receiving adjuvant chemoradiation. Of the 46 patients completing adjuvant treatment in‐house, contralateral neck was spared in 20%. There were no significant differences in survival, and patient‐reported outcomes in salivary function, mood, and anxiety were superior in those patients receiving unilateral neck radiation and directly correlated with mean dose to local structures. Conclusions: Surgery for OPC offers the potential for reduction in radiation volumes by omitting the contralateral neck in those who may have required definitive chemoradiation. Even in patients receiving concurrent chemotherapy, unilateral neck radiation has a favorable toxicity profile without compromising survival.